A eficácia da propaganda em realidade virtual do Atrativo Turístico Usina de Itaipu: uma proposta de instrumento para mensuração - Monica, Carolina Lima Della (2019)
The Technological advancement enables new forms of relationship and brand engagement with the customer. Thus, marketing practices evolve into the digital world, and in this context, the ability to foster deep customer engagement interactions is different for brands, which have Information and Communication Technologies (ICTs) as their allies to promote new experiments with mechanisms that make them more attractive and facilitated by multiple media. Tourism marketing in particular benefits from these technological advances as it is a highly dependent segment on the image and quality of information due to the intangibility of the services it offers. However, in Brazil there are few studies that analyze the impact of digital transformation on marketing and also as the emergence of new digital media, such as Virtual Reality (VR), which enables the creation of moments of brand engagement with consumers. Thus, the present study uses as object of study the advertising in RV of the tourist attraction “Usina de Itaipu” with the objective of proposing a marketing scale capable of measuring the effectiveness of an advertising in VR. The first step of this study was the literature review to identify the main variables that make up the “VR efficacy” construct; Then, a research instrument was elaborated and subjected to a pre-test with Survey survey in order to validate the scale. Therefore, a qualitative research was conducted with the key subjects in the creation of Itaipu's RV material and the results were analyzed together with the quantitative results. Thus, it was possible to improve the research instrument to allow the use of Exploratory Factor Analysis (EFA). The final application of the questionnaire took place at the Federal University of Rio de Janeiro with a sample of 238 students. Through EFA, the variables with the highest explanatory power were identified for each construct that resulted in the proposal of an instrument with 22 variables with 68% explanatory power and high internal consistency index. Finally, the effectiveness of Itaipu Plant RV advertising is measured and a promising instrument is proposed to measure the effectiveness of replicable RV tourist attraction advertising.